2014
DOI: 10.4238/2014.january.8.9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of associations between the TP53 Arg72Pro polymorphism with risk of head and neck carcinomas based on case-control studies

Abstract: ABSTRACT. Genetic factors have been shown to play a role in the development of head and neck cancers (HNCs). However, studies investigating the association between the TP53 Arg72Pro polymorphism and HNCs susceptibility have yielded conflicting results. Hence, we performed a meta-analysis of all eligible studies (up to January 1, 2012) to derive a more precise estimation of this association in order to increase understanding of the possible risk factors of HNCs. Twenty-seven casecontrol studies involving 3966 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…For example, Ren et al performed a meta-analysis to assess HNSCC risk and Arg72Pro TP53 mutation across various tumor sites in Asian and Caucasian cohorts. They found that this mutation was associated with increased risk of nasopharyngeal cancer, but not oral cancer, for homozygous, heterozygous and dominant model mutation comparisons in Caucasian cohorts but only homozygous mutations in Asian patients [ 127 ]. Given the frequency and complexity of TP53 aberration, further studies on the distinct role of this gene in specific epidemiological populations will be critical to developing an improved understanding of HNSCC pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ren et al performed a meta-analysis to assess HNSCC risk and Arg72Pro TP53 mutation across various tumor sites in Asian and Caucasian cohorts. They found that this mutation was associated with increased risk of nasopharyngeal cancer, but not oral cancer, for homozygous, heterozygous and dominant model mutation comparisons in Caucasian cohorts but only homozygous mutations in Asian patients [ 127 ]. Given the frequency and complexity of TP53 aberration, further studies on the distinct role of this gene in specific epidemiological populations will be critical to developing an improved understanding of HNSCC pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Future directions to evaluate etiologic causes in this seemingly low‐risk population could include the evaluation of epidermal growth factor receptor tumor levels, high levels of which are associated with reduced patient survival . Alternatively, HPV analysis combined with TP53 gene sequencing may suggest a possible viral component other than HPV for HPV− and TP53 wild‐type tumors …”
Section: Discussionmentioning
confidence: 99%
“…45 Alternatively, HPV analysis combined with TP53 gene sequencing may suggest a possible viral component other than HPV for HPV2 and TP53 wild-type tumors. 46,47…”
Section: Application Of Collins' Lawmentioning
confidence: 99%